2010
DOI: 10.5153/sro.2127
|View full text |Cite
|
Sign up to set email alerts
|

‘My Bed or Our Bed?’: Gendered Negotiations in the Sleep of Same-Sex Couples

Abstract: Sexuality as well as gender can be added to the range of socio-structural factors that influence the social patterning of sleep. This paper draws on in-depth interviews with 20 women and men aged between 45 – 65 years in same-sex couple relationships to examine how they negotiate their sleeping arrangements. The paper contends that gender differences are evident in how these negotiations are played out in the bedroom with women and men in same-sex relationships mirroring some of the patterns demonstrated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…In modern Western societies, sleep is commonly shared by spouses or romantic companions (Rosenblatt, 2006; Troxel, 2010). Several studies have explored the “dyadic nature of sleep” and couples’ experiences (e.g., Hislop, 2007; Kirkman, 2010; Luyster et al., 2016; Meadows, Arber, Venn, & Hislop, 2008; Strawbridge, Shema, & Roberts, 2004; Zarhin, 2016a), but further research is needed to understand the process of sleep interembodiment—how bodies are experienced as intertwined with the body of a sleep partner (Zarhin, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…In modern Western societies, sleep is commonly shared by spouses or romantic companions (Rosenblatt, 2006; Troxel, 2010). Several studies have explored the “dyadic nature of sleep” and couples’ experiences (e.g., Hislop, 2007; Kirkman, 2010; Luyster et al., 2016; Meadows, Arber, Venn, & Hislop, 2008; Strawbridge, Shema, & Roberts, 2004; Zarhin, 2016a), but further research is needed to understand the process of sleep interembodiment—how bodies are experienced as intertwined with the body of a sleep partner (Zarhin, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Most articles included some subjective method for assessing sleep quality (Afsahri et al, 2018; Costa et al, 2017; Dittami et al, 2007; Hislop, 2007; Junker et al, 2016; Khastar et al, 2020; Kirkman, 2010; Nozoe et al, 2014; Ogunbajo et al, 2020; Pallesen et al, 2020). Of these, eight articles used questionnaires (Afsahri et al, 2018; Costa et al, 2017; Junker et al, 2016; Khastar et al, 2020; Nozoe et al, 2014; Ogunbajo et al, 2020; Pallesen et al, 2020; Seehuus & Pigeon, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Again, inter‐rater agreement was examined by calculation of Cohen’s Kappa. Kappa was significant and ranged from 0.408 to 0.691 for most papers, with the exception of Dittami et al (2007), κ = 0.194, p = 0.222, and Kirkman (2010), κ = −0.111, p = 0.681.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…With the recent exception of Coveney (2014) who adopts semistructured interviews to examine the student sleep management experience, no intensive qualitative inquiry has been carried out to examine how university students actually experience sleep, see sleep as a meaningful activity, and articulate its situational conditions. This is despite the emergence of qualitative sleep research among and between other identified social groups such as sexes and genders (Hislop, 2007; Kirkman, 2010; Venn, 2007; Venn, Arber, Meadows, & Hislop, 2008), children and adolescents (Moran-Ellis & Venn, 2007; Williams, Lowe, & Griffiths, 2007), and older adults (Venn & Arber, 2011).…”
Section: Sleep and The University Student: Negotiating Rituals Of Oblmentioning
confidence: 99%